Yolngu Education, a Brief Background: Analysis of 5 Texts Concerning Yolngu Education in Arnhem Land, Northern Territory, Australia - Aleksandra Glabinska Kelly (University of Lower Silesia, 2016)
The paper analyzes pedagogical articles dealing with Yolngu and their knowledge status in the mainstream curriculum. My intent is to find out which arguments the authors use to broaden the curriculum with Indigenous knowledge. For this reason, I aim to answer two questions; how Yolngu people are constructed in texts, and which discourses can be unveiled in those texts. I use discourse analyses to deconstruct writers` issues and attitudes towards Indigenous knowledge and different approaches to integrating various traditions in day-to-day school experiences. I apply Norman Fairclough's methodology but concentrate mostly on the first, textual level. Critical linguistics is an additional tool to deepen the analyses that reveal the emancipatory discourse`s predominance.